Bimetallic Metal-Organic Framework-Derived Carbon Nanotube-Based Frameworks for Enhanced Capacitive Deionization and Zn-Air Battery - Shi, Wenhui; Xu, Xilian; Ye, Chenzeng; Sha, Dongyong; Yin, Ruilian; Shen, Xuhai; Liu, Xiaoyue; Liu, Wenxian; Shen, Jiangnan; Cao, Xiehong; Gao, Congjie (Frontiers in Chemistry, 2019)
Carbon-based materials have attracted intensive attentions for a wide range of energy and environment-related applications. Energy storage/conversion devices with improved performance have been achieved by utilization of metal-organic-framework (MOF)-derived carbon structures as active materials in recent years. However, the effects of MOF precursors on the performance of derived carbon materials are rarely investigated. Here, we report that the incorporation of small amount of Fe or Ni in Co-based MOFs leads to a significant enhancement for the derived carbon nanotube-based frameworks (CNTFs) in Na+/Cl- ion electrosorption. Further investigation revealed the enhanced performance is attributed to the improved specific surface area, electrical conductivity, and electrochemical activity. Notably, the CoFe-CNTF derived from bimetallic CoFe-MOFs exhibits a high ion adsorption capacity of 37.0 mg g−1, superior to those of most reported carbon materials. Moreover, the CoFe-CNTF also demonstrates high catalytic activity towards oxygen evolution reaction (OER) with a Tafel slop of 87.7 mV dec-1. After combination with three-dimensional graphene foam (3DG), the resultant CoFe-CNTF-coated 3DG is used as air-cathode for flexible all-solid-state Zn-air battery, which exhibits a high open circuit potential (1.455 V). Importantly, the fabricated flexible battery can light a light-emitting diode (LED) even when it is bent. This work provides new sights into designing high-performance and flexible electrode based on MOF-derived materials.